Developing the better and effective nursing education for improving transcultural nursing skills cultural competence and cultural sensitivity assessment tool (BENEFITS-CCCSAT) - Ayla Yava; Betül Tosun; Katalin Papp; Valérie Tóthová; Eda Şahin; Emel Bahadir Yılmaz; Ezgi Dirgar; Věra Hellerová; Sandra Tricas-Sauras; Mirko Prosen; Sabina Ličen; Igor Karnjus; et al. (BMC, 2023)
Abstract Background A clear need for the development of new comprehensive, reliable, sensitive and valid measurement tools to adequately asses the cultural competence and cultural sensitivity of nursing students exists. This study aimed to develop a new measurement tool to assess the nursing students' cultural competence and sensitivity. Methods This cross-sectional, instrument development study's first phase included postgraduate nursing students (n = 60) for the piloting study, and the second one included undergraduate nursing students (n = 459) for the main survey. This study used two data collection forms: The Student Descriptive Information Form and the Better and Effective Nursing Education for Improving Transcultural Nursing Skills Cultural Competence and Cultural Sensitivity Assessment Tool (BENEFITS-CCCSAT) draft. The content validity index was calculated using the Davis method. Cronbach's α coefficient and the item total correlation were calculated during the reliability analysis. The Kaiser-Meyer-Olkin (KMO) coefficient test, Bartlett significance test, and explanatory factor analysis (EFA) were used to evaluate the validity of the assessment tool. Results Scale validity and reliability analyses showed that the BENEFITS-CCCSAT included 26 items and five sub-dimensions: respect for cultural diversity; culturally sensitive communication; achieving cultural competence; challenges and barriers in providing culturally competent care; and perceived meaning of cultural care. Conclusion The BENEFITS-CCCSAT appears to be a valid and reliable instrument for measuring the cultural sensitivity and cultural competence of nursing students. This can be of great use, especially before attending clinical areas, and can offer both students and faculty reliable information to promote reflective and critical thinking, especially in areas where improvement is needed.